Sutureless Scleral Fixation of Intraocular Lens in Aphakia: Characteristics and Visual Outcomes: Oral Presentation - Observational Study - Resident - Supanji; Rahma, Fatkhati Saida; W., Firman S.; A, Angela Nurini; W, Tri Wahyu; Sasongko, M. Bayu (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesSutureless scleral fixation (SSF) surgery is one of the secondary intraocular lens (IOL) implantationprocedures for aphakic patients with absent or deficient capsular bag support that is beingincreasingly performed these days. This study aimed to describe the characteristics, indications for,and visual outcomes of patients who had undergone sutureless scleral fixation of intraocular lensesat Sardjito Hospital. MethodsA retrospective cross-sectional study of 43 eyes that SSF intraocular lens at Sardjito Hospital,Yogyakarta. The data were collected from electronic medical records of patients from October 2020to December 2022. The data were analyzed descriptively by presenting numbers and percentages forcategorical variables and mean ± standard deviation (SD) for numerical variables. Outcomesincluded pre- and postoperative uncorrected visual acuity (UCVA). ResultsThere were 43 eyes obtained from 40 patients who underwent SSF intraocular lens in this study,consisting of 35 males (79.55%) and 9 females (20.45%). The mean age of the subjects was 50.04 ±19.2 years. Lens subluxation was the most common indication for surgery (32.5%), followed bydropped nucleus (20.45%), intraocular lens luxation (18.18%), lens luxation (15.91%), intraocularlens decentration (9.09%), and endophthalmitis (4.55%). Before surgery, most of the patients hadvisual acuity of less than 3/60 (81.4%) and after surgery, 32.56% had ?6/18, 34.88% had <6/18-6/60,and 18.60% had <6/60-3/60. ConclusionMales predominantly underwent SSF intraocular lens surgery at Sardjito Hospital. Lens subluxationwas the most common indication for the surgery. There was an improvement in visual outcome.